Ayurveda Management Of Garavishjanit Amlapitta: A Case Study - Bhati , Lokesh Singh; Sharma, Madan Mohan; Porwal, Rohit R (International Research Journal of Ayurveda & Yoga, 2020)
People are not following dietary disciplines which suits for their health. Many of fast food substances, unhealthy eating habits fall under Viruddhaahar. Amlaguna property of the pitta is exaggerated. Acharya Charaka mentions the diseases which created from consumption of Viruddhaahar. Repeated consumption of viruddhaahar leads to agnidushti and such dushtagni is unable to digest even light food. Indigested food forms aamvisha. Amavisha probably has the nature of Garavisha.Ama combines with vitiated pitta and this sthansamshrya occurs in Aamsaya leading to Amlapitta. Hetu and Vyadhi viparit chikitsa becomes pivotal part in treatment of Garavishajanit Amlapitta. The Chikitsa Principles are shodhan in the form of Vaman and Virechan and then shaman chikitsa. But in the current clinical practice, Shaman Chikitsa is also preferred in Amlapitta. So we will work out on shaman remedies to be tested for effectiveness in Garavishjanit Amlapitta. Sootshekhar Ras is clinically proven remedy and used in the treatment of Amlapitta. Suvarna is one of the main ingredients in Sootshekhar Ras which is stated as vishdoshhar and used in the treatment of garavisha, soit is hetuviparit. The ingredients of which are the drugs agnivruddhi and pittadoshasanshamanproperty. Thus can be used as shaman remedy in Garavishajanit Amlapitta. The result revealed significant effect of Sootshekhar Ras in various subjective parameters like avipak, klama, utklesh, tikta-amla udgar,hruda-kantha dah and aruchi after treatment.